Patiromer for the management of hyperkalemia in heart failure with reduced ejection fraction: the DIAMOND trial . (23rd August 2022) - Butler, Javed; Anker, Stefan D; Lund, Lars H; Coats, Andrew J S; Filippatos, Gerasimos; Siddiqi, Tariq Jamal; Friede, Tim; Fabien, Vincent; Kosiborod, Mikhail; Metra, Marco; Piña, Ileana L; Pinto, Fausto; et al.
Abstract: Aims: To investigate the impact of patiromer on the serum potassium level and its ability to enable specified target doses of renin–angiotensin–aldosterone system inhibitor (RAASi) use in patients with heart failure and reduced ejection fraction (HFrEF). Methods and results: A total of 1642 patients with HFrEF and current or a history of RAASi-related hyperkalemia were screened and 1195 were enrolled in the run-in phase with patiromer and optimization of the RAASi therapy [≥50% recommended dose of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker/angiotensin receptor-neprilysin inhibitor, and 50 mg of mineralocorticoid receptor antagonist (MRA) spironolactone or eplerenone]. Specified target doses of the RAASi therapy were achieved in 878 (84.6%) patients; 439 were randomized to patiromer and 439 to placebo. All patients, physicians, and outcome assessors were blinded to treatment assignment. The primary endpoint was between-group difference in the adjusted mean change in serum potassium. Five hierarchical secondary endpoints were assessed. At the end of treatment, the median (interquartile range) duration of follow-up was 27 (13–43) weeks, the adjusted mean change in potassium was +0.03 mmol/l in the patiromer group and +0.13 mmol/l in the placebo group [difference in the adjusted mean change between patiromer and placebo: −0.10 mmol/l (95% confidence interval, CI −0.13, 0.07); P < 0.001]. Risk of hyperkalemia >5.5 mmol/l [hazard ratio (HR) 0.63; 95% CI 0.45, 0.87; P = 0.006), reduction of MRA dose (HR 0.62; 95% CI 0.45, 0.87; P = 0.006), and total adjusted hyperkalemia events/100 person-years (77.7 vs. 118.2; HR 0.66; 95% CI 0.53, 0.81; P < 0.001) were lower with patiromer. Hyperkalemia-related morbidity-adjusted events (win ratio 1.53, P < 0.001) and total RAASi use score (win ratio 1.25, P = 0.048) favored the patiromer arm. Adverse events were similar between groups. Conclusion: Concurrent use of patiromer and high-dose MRAs reduces the risk of recurrent hyperkalemia (ClinicalTrials.gov: NCT03888066). Structured Graphical Abstract: Structured Graphical Abstract Study design, primary and secondary endpoints of the DIAMOND trial.